Evolution of the Solid Human Tumor Cells Properties in Various Experimental Systems in Vitro - Anna B. Danilova; Natalia A. Efremova; Anna A. Murashkina; Tatiana L. Nekhaeva; Mykhail A. Maydin; Ekaterina S. Artemyeva; Anna S. Artemyeva; Irina A. Baldueva (Journal of Hematology and Oncology Research, 2022)
Background Human malignant cell models which reflect the structural and physiological complexity of tumor tissue are of great importance for preclinical research in oncology. Spheroids/tumoroids derived from solid tumors are of great interest as cellular models mimicking the first vascular-free growth phase of a tumor node. The fact of the identity between artificially created tumor multicellular aggregates and the real tumor tissue, however, needs to be specified, described and validated in order to see how closely the spheroids are biologically similar to the malignized tissues in vivo compared to the monolayer cell cultures traditionally used. We present here a comparison study of the characteristics of solid tumor cells of different histogenesis (melanomas, soft tissue sarcomas and bone sarcomas, epithelial tumors) cultured in two dimensions (monolayer culture) and three dimensional space (spheroid), namely: spatial organization, multiplication, metabolic activity. Patients and Methods For the creation of 2 D and 3D cell models the cells isolated from the patient's solid tumor fragments obtained intraoperatively were used. 15 samples of skin melanoma, 20 samples of soft tissue and osteogenic sarcomas (STBS), and 9 samples of epithelial tumors (ET). The tumor cells were all cultivated for at least 10 passages. We used phase contrast, confocal microscopy, and immunohistochemistry to investigate spheroids and monolayer cultures. The supernatants of tumor cells grown in 2D and 3D cultures were studied using ELISA and multiplex analysis for the production of a spectrum of chemokines and cytokines supporting the immunosuppression, invasion and metastasis processes. Results Tumor specimens received were predominantly of metastatic origin (75%). In 100% of cases 2D cultures were received, in 88.6% of cases (39 out of 44) we succeeded in obtaining spheroids. There was no direct correlation between the efficiency of tumoroid formation and the tumor's histogenetic origin and the stage of the cancer process (primary tumor, recurrence, metastasis). The median size of spheroids by 4-5 days of cultivation with a starting concentration of 10000 cells per well was 657.14 μm for melanoma (min 400 - max 1000 μm), 571.42 μm (min 400 - max 700 μm), 507.14 μm (min 300 - max 600 μm) for soft tissue sarcomas, 650.0 μm (min 400 - max 900 μm) for osteogenic sarcomas. Immunochemical analysis of Ki-67, GLUT1, and Ecadherin markers was carried out for tumor tissue samples, single-layer tumor cultures, and tumoroids of every patient. The distribution of the stained groups in the spheroids was distinct from the monolayer cultures and more in accordance with the distribution of such in the tissue tumor, the number of Ki-67+ cells was increasing in the spheroids. We detected no dependence of Ki-67+ and GLUT1+ cell localization grade on spheroid size. We identified E-cadherin in tumor tissue and tumoroids of breast carcinoma and one melanoma culture. Monolayer cultures did not express it. The increase in secretory cell activity of the solid tumor cells from 2D to 3D system was observed when CCL2, CCL3, CXCL1, CXCL16, MIF, IL10, MICA (p<0.01) were investigated. Conclusion The presence of patient-specific cells of solid tumors in a 3D environment causes activation of the proliferative and metabolic processes as compared to monolayer cultures, which makes these models approximate the real world clinical picture. The production of chemokines that can attract to the tumor various types of immune system cells, to include their immature versions, as well as production of cytokines and Immunosuppression factors that, when present in the tumor microenvironment in the high concentrations, contribute to the formation of immune cells having suppressive capacities occurs in the 3D cell system. Three-dimensional model of the initial tumor nodule formation stage thus demonstrates the forming process of tumor cells favorable for them microenvironment. Construction of three-dimensional models - spheroids of tumor cells of differing histogenesis demands individual approach and more thorough investigation.
Keywords: Spheroids